Complete MHC Haplotype Sequencing for Common Disease Gene Mapping - Stewart, C. Andrew; Horton, Roger; Allcock, Richard J.N.; Ashurst, Jennifer L.; Atrazhev, Alexey M.; Coggill, Penny; Dunham, Ian; Forbes, Simon; Halls, Karen; Howson, Joanna M.M.; Humphray, Sean J.; Hunt, Sarah; et al. (Genome Research, 2004)
The future systematic mapping of variants that confer susceptibility to common diseases requires the construction of a fully informative polymorphism map. Ideally, every base pair of the genome would be sequenced in many individuals. Here, we report 4.75 Mb of contiguous sequence for each of two common haplotypes of the major histocompatibility complex (MHC), to which susceptibility to >100 diseases has been mapped. The autoimmune disease-associated-haplotypes HLA-A3-B7-Cw7-DR15 and HLA-A1-B8-Cw7-DR3 were sequenced in their entirety through a bacterial artificial chromosome (BAC) cloning strategy using the consanguineous cell lines PGF and COX, respectively. The two sequences were annotated to encompass all described splice variants of expressed genes. We defined the complete variation content of the two haplotypes, revealing >18,000 variations between them. Average SNP densities ranged from less than one SNP per kilobase to >60. Acquisition of complete and accurate sequence data over polymorphic regions such as the MHC from large-insert cloned DNA provides a definitive resource for the construction of informative genetic maps, and avoids the limitation of chromosome regions that are refractory to PCR amplification.
10.1101/gr.2188104